'When the doors of Hell close': Dimensions of well-being and positive adjustment in a group of Palestinian children living amidst military and political violence. (February 2015) - Veronese, Guido; Castiglioni, Marco
Palestinian children living amidst political and military violence are often labeled as affected by post-traumatic stress syndromes. Some researchers report that a majority of Palestinian children suffer from post-traumatic stress disorder and other stress-related psychiatric impairments in the wake of military incursions and bombings. On the other hand, data from field research and clinical experience show that these children continue to display positive functioning in terms of adjustment to trauma, despite the adverse environmental conditions. This article reports on qualitative research with children from two refugee camps in the West Bank, Occupied Palestinian Territories: Nur Shams and Tulkarm. Thematic content analysis was applied to narratives and written materials produced by 74 school-age children during two summer camps held in the Tulkarm region in 2010 and 2011. The aims of the study were: (a) to explore the domains of well-being that help children cope with violence and insecurity and (b) to investigate whether experiential activities focused on emotional and relational competences influenced children's self-perceived well-being. Personal, environmental, micro- and macro-social factors were identified as playing a role in well-being. The article discusses the limitations of the study and its implications for clinical and community work with children exposed to political and military threat.